Reconstructing al-Farghānī’s Southern Astrolabe: A Philological and Astronomical Study for Equatorial Observations in Indonesia - Fajrullah Fajrullah; Nur Faizah (Al-Hilal: Journal of Islamic Astronomy, 2026)
This study reconstructs al-Farghānī’s concept of the southern astrolabe through an interdisciplinary approach combining Arabic philology and computational astronomy. Focusing on the sixth chapter (al-Naw’ al-Sādis) of Kitāb al-Asturlāb, the research aims to examine the technical relevance of the southern astrolabe for equatorial observations in Indonesia. The study employs philological methods, including codicological description, transliteration, textual emendation, and annotated translation, integrated with stereographic projection analysis and astronomical computation. The findings demonstrate that the conventional northern astrolabe produces severe geometric distortion when representing southern celestial objects at low latitudes, causing major navigational stars to fall beyond the instrument’s physical limits. In contrast, the southern astrolabe provides a proportional projection of southern stars within the equatorial circle, making it more suitable for observers in the Indonesian archipelago. This study contributes to the historiography of Islamic astronomy by demonstrating the continued scientific relevance of al-Farghānī’s geometrical framework for contemporary equatorial Islamic astronomy studies.